Implementasi Keadilan Restoratif Terhadap Penyelesaian Tindak Pidana di Wilayah Polres Malang - Mustofa, Choirul (Postgraduate University of Merdeka Malang, 2024)
Restorative justice emerged from the concept of criminal law reform. The Indonesian Criminal Code (KUHP) and the Criminal Procedure Code (KUHAP) do not recognize the concept of out-of-court/non-litigation resolution. Therefore, when there is a reconciliation between the disputing parties, the case does not necessarily have to proceed to court. Throughout 2021 until March 2022, the Indonesian National Police (Polri) resolved 15,039 cases using restorative justice, an increase of 28.3% from the previous year's 9,199 cases. The main principle of restorative justice is law enforcement that always prioritizes restoring the situation to its original state and reinstating good relationships within the community. Based on the background description, this article examines and analyzes the implementation of restorative justice and the obstacles to resolving criminal offenses at the investigation and inquiry levels at the Malang Resort Police. This research is an empirical legal study, collecting primary data sources in the Malang Police jurisdiction. Data indicate that resolutions through restorative justice have increased each year: 2019: 2,415 reports, 180 cases (7.5%) resolved; 2020: 1,517 reports, 226 cases (14.9%) resolved; 2021: 1,263 reports, 160 cases (12.7%) resolved; 2022: 1,065 reports, 209 cases (19.6%) resolved; 2023: 1,140 reports, 273 cases (23.6%) resolved. This increase has a positive impact as it aligns with the principles of criminal justice that are simple, quick, and low-cost, avoiding the necessity to bring cases to trial. The main obstacle in implementing restorative justice is the failure to reach a peace agreement between the victim and the perpetrator.